Legal Protection of Elderly Workers in Indonesia’s Food and Beverage Sector: A Normative Comparative Study with Australia - Aveyory, Immanuela Yvette (Al-Risalah, 2025)
This research examines legal protection and social security for elderly workers in the Food and Beverage (F&B) sector in Indonesia with a normative and comparative legal approach. The main problem identified is the absence of specific regulations that explicitly protect the rights of elderly workers, especially those who work in the informal sector. Sakernas 2023 data shows that the majority of elderly workers receive substandard wages, long working hours, and minimal access to social security. This study uses a comparative method with the Australian legal system, where the Fair Work Act 2009 explicitly prohibits age discrimination and provides comprehensive legal protection and social security. The analysis found that Indonesia still faces normative gaps, multiple regulatory interpretations, and overlapping labour and social protection policies. The research recommendations emphasise the importance of regulatory reform, strengthening the social security system, as well as more optimal education and supervision. With these steps, it is expected that elderly workers in the F&B sector can work safely, with dignity, and obtain proper social rights in accordance with the times. The results of this study are expected to be an important contribution for policy makers and business actors in Indonesia.